Identificación de las condiciones de seguridad y salud y las medidas de intervención requeridas para los trabajadores dedicados a las extracción y explotación marmolera en el departamento del Huila (2020)
The present investigation is carried out in the department of Huila, with the objective of identifying the safety and health conditions and the intervention measures required for the workers dedicated to the extraction and exploitation of marble in the department of Huila, said identification is carried out based on the new ISO 45001 standard, also the identification of hazards, evaluation, risk assessment and determination of control measures according to risks, using the methodology set out in GTC 45 of 2010.